2016
DOI: 10.21767/2172-0479.100040
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Antibacterial and Cytotoxic Potentials of Bioactive Metabolites Extracted from Padina tetrastromatica

Abstract: Marine brown algae, Padina tetrastromatica was extracted using diverse organic solvents of increasing polarity such as diethyl ether, chloroform, acetone, dichloromethane: methanol and methanol. The obtained extracts were evaluated for antibacterial and brine shrimp cytotoxicity assays. It was found that methanolic extract of P. tetrastromatica exhibited the broadest and highest range of antibacterial activity. In cytotoxic activity, the methanolic extract of P. tetrastromatica showed significant activity (LD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The obtained extracts were evaluated for antibacterial assays. It was found that methanolic extract (The most polar one) of P. tetrastromatica demonstrated the broadest and highest range of antibacterial activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained extracts were evaluated for antibacterial assays. It was found that methanolic extract (The most polar one) of P. tetrastromatica demonstrated the broadest and highest range of antibacterial activity (28).…”
Section: Discussionmentioning
confidence: 99%